Tumor purity–associated genes influence hepatocellular carcinoma prognosis and tumor microenvironment - Zhao, Yan; Xu, Xu; Wang, Yue; Wu, Lin D.; Luo, Rui L.; Xia, Ren P. (Frontiers in Oncology, 2023)
Tumor purity plays an important role in the progression of solid tumors. We aimed to explore potential prognostic genes associated with tumor purity in hepatocellular carcinoma (HCC) by bioinformatics analysis. The ESTIMATE algorithm was applied to determine the tumor purity of HCC samples from The Cancer Genome Atlas (TCGA). the differentially expressed tumor purity-related genes (DEGs) were identified based on differential expression analysis, weighted gene coexpression network analysis (WGCNA), and overlap analysis. The Kaplan-Meier (K-M) survival analysis and Least Absolute Shrinkage and Selection Operator (LASSO) regression analyses were performed to identify prognostic genes for the prognostic model construction. The expression of these genes was further validated by the GSE105130 dataset from the Gene Expression Omnibus (GEO) database. We also characterized the clinical and immunophenotypes of prognostic genes. Gene Set Enrichment Analysis analysis was performed to explore the biological signaling pathway. A total of 26 tumor purity-related DEGs were identified, which were involved in biological processes such as immune/inflammatory responses and fatty acid elongation. Ultimately, we identified ADCK3, HK3, and PPT1 as the prognostic genes for HCC. Moreover, HCC patients exhibiting higher expression of ADCK3 and lower expression of HK3 and PPT1 had a better prognosis. Furthermore, high expression of HK3 and PPT1 and low expression of ADCK3 resulted in high tumor purity, high immune score, high stromal score, and high ESTIMATE score. GSEA showed that these prognostic genes were closely correlated with immune-inflammatory response, tumor growth, and fatty acid production/degradation. This study identified novel predictive biomarkers and preliminarily explores the underlying molecular mechanisms of HCC pathology. Current evidence suggests that ADCK3, HK3, and PPT1 may contribute to the prognostic workup of HCC and play a complementary role in determining tumor purity phenotypes.